Functional recovery of patients with ischemic cardiomyopathy treated with coronary artery bypass surgery and concomitant intramyocardial bone marrow mononuclear cell implantation – A long-term follow-up study - Trifunović, Zoran Života; Obradović, Slobodan; Balint, Bela; Ilić, Radoje; Vukić, Zoran; Šišić, Marija; Kostić, Jelena; Rusović, Siniša; Dobrić, Milan; Ostojić, Gordana (Vojnosanitetski pregled, 2015)
Background/Aim. Intramyocardial bone marrow mononuclear cells (BMMNC) implantation concomitant to coronary artery bypass grafting (CABG) surgery as an option for regenerative therapy in chronic ischemic heart failure was tested in a very few number of studies, with not consistent conclusions regarding improvement in left ventricular function, and with a follow-up period between 6 months and 1 year. This study was focused on testing of the hypothesis that intramyocardial BMMNC implantation, concomitant to CABG surgery in ischemic cardiomyopathy patients, leads to better postoperative long-term results regarding the primary endpoint of conditional status-functional capacity and the secondary endpoint of mortality than CABG surgery alone in a median follow-up period of 5 years. Methods. A total of 30 patients with ischemic cardiomyopathy and the median left ventricular ejection fraction (LVEF) of 35.9 ± 4.7% were prospectively and randomly enrolled in a single center interventional, open labeled clinical trial as two groups: group I of 15 patients designated as the study group to receive CABG surgery and intramyocardial implantation of BMMNC and group II of 15 patients as the control group to receive only the CABG procedure. All the patients in both groups received the average of 3.4 ± 0.7 implanted coronary grafts, and all of them received the left internal mammary artery (LIMA) to the left anterior descending (LAD) and autovenous to other coronaries. Results. The group with BMMNC and CABG had the average of 17.5 ± 3.8 injections of BMMNC suspension with the average number of injected bone marrow mononuclear cells of 70.7 ± 32.4 × 106 in the total average volume of 5.7 ± 1.5 mL. In this volume the average count of CD34+ and CD133+ cells was 3.96 ± 2.77 × 106 and 2.65 ± 1.71 × 106, respectively. All the patients were followed up in 2.5 to 7.5 years (median, 5 years). At the end of the follow-up period, siginificantly more patients from the group that received BMMNC were in the functional class I compared to the CABG only group (14/15 vs 5/15; p = 0.002). After 6 months the results on 6-minute walk test (6-MWT) were significantly different between the groups (435 m in the BMMNC and CABG group and 315 m in the CABG only group; p = 0.001), and continued to be preserved and improved on the final follow-up (520 m in the BMMNC and CABG group vs 343 m in the CABG only group; p
Keywords: coronary artery bypass; bone marrow transplantation; myocardium; intraoperative period; physical endurance; mortality